Preparation method of sodium battery positive electrode material

During the preparation of sodium electropositive electrode material, a low-sodium ratio positive electrode material is laid on the bottom of the cassette and a high-sodium ratio raw material is loaded on it, the corrosion problem caused by the reaction of sodium source and the cassette is solved, extending the service life of the cassette and maintaining the electrical properties of the material.

CN119551739AActive Publication Date: 2025-03-04XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411735793.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

In the existing preparation methods of sodium electropositive electrode materials, the high-temperature sintering process causes the sodium source to react with the sachet, causing the sachet to corrosion and shorten the service life.

Method used

A low-sodium-specific positive electrode material (sintered material) is laid on the bottom of the cassette, and a high-sodium-specific raw material (mixed material) is loaded thereon to form a sodium-electric positive electrode material through sintering. This method reduces direct reaction with the sachet by providing a sodium vacancy so that the sodium ions in the high-sodium ratio feedstock are received.

Benefits of technology

It effectively extends the service life of the sachet, maintains the electrical properties of the sodium-electric positive electrode material, and avoids corrosion of the sachet by the sodium source.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551739A_ABST
    Figure CN119551739A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly provides a preparation method of a sodium battery positive electrode material, which comprises the following steps: (1) providing a sintered material and a mixed material, the sintered material being a sintered product of a sodium source and a metal precursor, the molar ratio of the amount of the sodium source to the amount of the metal precursor being a in terms of Na / Me; the mixture is a mixture of a sodium source and a metal precursor, and the molar ratio of the amount of the sodium source to the amount of the metal precursor is b in terms of Na / Me; a is equal to 0.4 to 0.7, and b is equal to 0.9 to 1.1; (2) sagger charging is conducted, specifically, a layer of sintered material is laid at the bottom in a sagger, then a mixture is loaded on the sintered material, the sagger is cut into blocks, the charging sagger is obtained, the thickness of the sintered material is h1, the thickness of the mixture is h2, and h1 and h2 meet the following relational expression that h2 / h1 is larger than or equal to 5 and smaller than or equal to 18; and (3) sintering the charging saggar to form the sodium battery positive electrode material. According to the preparation method, the service life of the sagger can be effectively prolonged while the electrical property of the sodium battery positive electrode material is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of batteries, and specifically provides a method for preparing a sodium battery positive electrode material. Background Art

[0002] Secondary batteries represented by sodium-ion batteries have been applied in many fields such as electric vehicles, energy storage power systems (such as hydropower, thermal power, wind power and solar power stations, etc.). Compared with lithium-ion batteries, sodium-ion batteries have significant raw material cost advantages, especially for cathode materials, which account for a large proportion of the cost. The sodium source reserves, which are the main raw materials of sodium cathode materials, are more abundant, which makes sodium-ion batteries have good application prospects in large-scale energy storage fields such as energy storage grids.

[0003] At present, the main preparation method of sodium positive electrode materials includes high-temperature solid-phase sintering process. In the sintering process, the positive electrode precursor and the sodium source are placed in a sagger. After sintering, the sintered material block is separated from the sagger, and the sagger is recycled to produce positive electrode materials again. However, the sintering temperature usually used in this process is much higher than the melting point of the sodium source, which makes the sodium source in a molten state and corrodes the sagger. It is very easy to react with the components in the sagger and affect the service life of the sagger. This phenomenon is more obvious when preparing sodium positive electrode materials with high sodium ratio raw materials. For example, in a ceramic sagger with alumina as the main chemical component, the molten sodium source in the high sodium ratio raw material easily reacts with alumina to form sodium nepheline, causing the volume of the sagger to expand, which is very easy to cause the sagger to crack and be damaged, and the service life is shortened.

[0004] CN108649216A discloses a method for preparing a nickel-cobalt-manganese-oxide lithium positive electrode material, comprising: uniformly mixing raw materials including lithium compounds and nickel-cobalt-manganese precursors, placing the raw materials in a sagger with at least one layer of filter paper laid flat on the bottom, sintering and crushing to obtain a nickel-cobalt-manganese-oxide lithium material. Although the introduction of filter paper can delay the damage of the sagger to a certain extent, the filter paper will burn at a high temperature of about 600°C, and the protective effect on the sagger is limited. Instead, some impurities will be introduced, which seriously affects the performance of the positive electrode material. In addition, compared with the preparation of lithium battery positive electrode materials, the loss of the sagger in the preparation of sodium battery positive electrode materials is more serious. On the one hand, due to the larger radius and stronger alkalinity of sodium ions, the sodium source erodes the sagger more seriously; on the other hand, the sodium source has stronger permeability during the sintering process and is more likely to penetrate into the pores of the sagger.

[0005] CN117342629A discloses a method for preparing a sodium ion battery positive electrode material with low surface residual alkali content, comprising: mixing a sodium source, a precursor and an M source (M is selected from Al, Ti, etc.) to obtain a mixture; placing the mixture in a coated sagger for sintering to obtain a positive electrode material, wherein the coating on the sagger includes oxides such as MgO, CaO, and TiO2. This method can reduce the loss of the sodium source, but the cost of the sagger is higher by modifying the sagger to coat its surface, and the coating is easy to fall off after multiple sintering, and the improvement effect on the sagger is limited.

[0006] Therefore, it is urgent to develop a new method for preparing a sodium-based cathode material that can extend the service life of the sagger. Summary of the invention

[0007] The purpose of the present application is to provide a method for preparing a sodium positive electrode material, which can effectively extend the service life of the sagger without affecting the electrical properties of the sodium positive electrode material.

[0008] To achieve the above objectives, the present application provides a method for preparing a sodium positive electrode material, comprising:

[0009] (1) Provide sintering materials and mixed materials

[0010] The sintering material is a sintering product of a sodium source and a metal precursor, and the molar ratio of the sodium source to the metal precursor is Na / Me, which is a;

[0011] The mixed material is a mixture of a sodium source and a metal precursor, and the molar ratio of the sodium source to the metal precursor is calculated as b with Na / Me;

[0012] a=0.4~0.7,b=0.9~1.1,Me represents the metal element in the metal precursor;

[0013] (2) Sagger loading

[0014] A layer of sintering material is laid on the bottom of the sagger, and then the mixed material is loaded on the sintering material, and the mixed material is cut into pieces to obtain a loading sagger;

[0015] In the charging sagger, the thickness of the sintering material is h1, the thickness of the mixed material is h2, and h1 and h2 satisfy the following relationship: 5≤h2 / h1≤18;

[0016] (3) sending the loading sagger to a sintering furnace for sintering to obtain the sodium positive electrode material.

[0017] In the preparation method of the present application, a low-sodium ratio positive electrode material (sintering material) is laid at the bottom of the sagger, and the material has sodium vacancies, so that during sintering, part of the sodium ions in the high-sodium ratio raw material (mixture) located thereon can be received to generate the required sodium-based positive electrode material; in addition, due to the sodium-deficient characteristics of the low-sodium ratio positive electrode material, it basically does not react directly with the sagger, so the corrosion degree of the loading sagger can be significantly reduced.

[0018] In some embodiments of the present application, in the charging sagger, the thickness of the sintering material is h1, which is 5 to 15 mm, the total thickness of the charging material is h=h1+h2, and h is 70 to 100 mm.

[0019] In some embodiments of the present application, the metal element Me in the metal precursor is selected from one or more of Ni, Fe, Mn, Co, Al, Ti, Mg, Ca, Zn, Cu, W and La.

[0020] Furthermore, the metal precursor is a nickel-containing ternary precursor.

[0021] Furthermore, the chemical formula of the nickel-containing ternary precursor is Ni x M y A 1-x-y (OH)2, wherein M is Fe or Co, A is Mn or Ti, 0.2≤x≤0.6, 0.1<y<0.4.

[0022] In some embodiments of the present application, the sodium source is sodium carbonate and / or sodium hydroxide.

[0023] In some embodiments of the present application, the sintering material is prepared by a method comprising the following steps:

[0024] In the presence of an oxygen-containing atmosphere, the sodium source and the metal precursor are subjected to high-temperature calcination and crushing to powder; wherein the high-temperature calcination temperature is 800-900° C. and the time is 15-30 hours.

[0025] In some embodiments of the present application, the sintering is performed in an oxygen-containing atmosphere, the sintering temperature is 900 to 1000° C., and the sintering time is 15 to 30 hours.

[0026] In some embodiments of the present application, the sintering furnace is a high-temperature roller furnace, the high-temperature roller includes a sintering zone, and the temperature of the sintering zone is 900-1000°C.

[0027] In some embodiments of the present application, the sagger is a ceramic sagger.

[0028] Furthermore, the material of the ceramic sagger includes at least two of cordierite, mullite and spinel.

[0029] In some embodiments of the present application, a=0.45-0.7, b=0.95-1.05, 6<h2 / h1≤16. In this case, the number of times the sagger is used can be further increased and the sodium positive electrode material can maintain a high capacity.

[0030] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0032] Figure 1 This is a schematic diagram of sagger loading according to one embodiment of the present application;

[0033] Figure 2 The XRD diagrams of the sodium positive electrode materials prepared in Comparative Example 1, Comparative Example 3 and Example 2. DETAILED DESCRIPTION

[0034] The following describes the implementation of the present application in detail. The implementation described below is exemplary and is only used to explain the present application, and cannot be understood as limiting the present application.

[0035] The "range" disclosed in the present application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form an unclearly recorded range, and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0036] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0037] The present application provides a method for preparing a sodium ion positive electrode material, the method comprising:

[0038] (1) Provide sintering materials and mixed materials

[0039] The sintering material is a low sodium ratio positive electrode material, specifically a sintering product of a sodium source and a metal precursor, and the molar ratio of the sodium source to the metal precursor is calculated as Na / Me, a=0.4-0.7,

[0040] The mixed material is a mixture of a sodium source and a metal precursor, and the molar ratio of the sodium source to the metal precursor is calculated as b, where b=0.9-1.1.

[0041] Me represents the metal element in the metal precursor;

[0042] (2) Sagger loading

[0043] A layer of sintering material is laid on the bottom of the sagger, and then the mixed material is loaded on the sintering material, and the mixed material is cut into pieces to obtain a loading sagger;

[0044] (3) sending the loading sagger to a sintering furnace for sintering to form a sodium positive electrode material.

[0045] The inventors of the present application have found in their research that in the process of preparing sodium positive electrode materials using a high-temperature sintering process with a high sodium ratio as raw material, high-concentration sodium ions will inevitably diffuse into the pores of the sagger in contact with it and react with the sagger components to cause corrosion and cracking of the sagger. Accordingly, before the high-sodium ratio raw material (mixture) is loaded into the sagger for sintering, the present application first lays a layer of low-sodium ratio positive electrode material (sintering material) at the bottom of the sagger to provide more sodium vacancies, so that during the sintering process, part of the sodium ions in the high-sodium ratio raw material can diffuse to the low-sodium ratio positive electrode material area at the bottom, and are received by the sodium vacancies to generate positive electrode materials with increased sodium ratios, and because of its sodium-deficient characteristics, the low-sodium ratio positive electrode material at the bottom will not react with the sagger, effectively increasing the number of times the sagger is used.

[0046] In the present application, the sodium source may be an inorganic substance containing sodium, such as sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium chloride, etc. According to some embodiments, the sodium source is sodium hydroxide and / or sodium carbonate.

[0047] In the present application, the metal precursor may include one or more metal elements Me other than Na.

[0048] In some embodiments, the metal element Me in the metal precursor may be selected from one or more of Ni, Fe, Mn, Co, Al, Ti, Mg, Ca, Zn, Cu, W and La.

[0049] In the present application, the metal precursor can be selected from various metal sources (ie, Me source), for example, one or more metal raw materials such as nickel source, manganese source, iron source, cobalt source, etc., or it can be a multi-element precursor containing multiple metal elements at the same time.

[0050] Preferably, the metal precursor is a nickel-containing ternary precursor, such as nickel-iron-manganese hydroxide, nickel-iron-cobalt hydroxide, or nickel-manganese-titanium hydroxide.

[0051] Preferably, the chemical formula of the nickel-containing ternary precursor is Ni x M y A 1-x-y (OH)2, wherein M is Fe or Co, A is Mn or Ti, 0.2≤x≤0.6, 0.1<y<0.4.

[0052] As some examples, the metal precursor is Ni 0.34 Fe 0.33 Mn 0.33 (OH)2 or Ni 0.34 Co 0.33 Mn 0.33 (OH)2.

[0053] In the present application, in the sintering material, the molar ratio of the sodium source to the metal precursor is Na / Me, a=0.4-0.7, for example, 0.4, 0.45, 0.55, 0.57, 0.58, 0.60, 0.62, 0.65, 0.67, 0.7, etc. The sodium deficiency feature of the sintering material can prevent the charging sagger from reacting with the sagger during the sintering process, and can provide sufficient sodium vacancies on the other hand, so that the sodium ions in the mixed material flow to supplement the sodium vacancies.

[0054] In the present application, it can be understood that when the metal precursor has one metal element, Me represents the metal element; when the metal precursor has multiple metal elements, Me represents all of these metal elements. For example, when the metal precursor is Ni 0.34 Fe 0.33 Mn 0.33 In the case of (OH)2, Me represents Ni, Fe and Mn, and Na / Me refers to the molar ratio between Na provided by the sodium source and the sum of Ni, Fe and Mn provided by the metal precursor.

[0055] In some embodiments, the sintering material is prepared by a method including the following steps: high-temperature calcining and crushing a sodium source and a metal precursor in the presence of an oxygen-containing atmosphere; wherein the high-temperature calcination temperature is 800-900°C (for example, 800°C, 810°C, 820°C, 850°C, 870°C, 900°C, etc.), and the high-temperature calcination time is 15-30h (for example, 15h, 18h, 20h, 24h, 26h, 28h, 30h, etc.).

[0056] In the present application, the oxygen-containing atmosphere may be, for example, oxygen, high-concentration oxygen (concentration ≥ 70%), or carbon-free air (CO2 content ≤ 50 ppm).

[0057] In the present application, the sintering material is in powder form. Generally, the smaller and more uniform the particle size, the more conducive it is to compaction and to promote the isolation of the mixed material from the sagger. Generally, the median particle size Dv of the sintering material is 50 It can be 5 to 10 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, etc.

[0058] In the present application, the molar ratio of the sodium source to the metal precursor in the mixture is calculated as Na / Me, b=0.9-1.1, for example, 0.9, 0.92, 0.95, 0.97, 0.98, 1, 1.02, 1.05, 1.06, 1.08, 1.1, etc. Preferably, the types of the sodium source and the metal precursor in the mixture are the same as those in the sintering material. In this way, the possibility of stratification of the product can be reduced.

[0059] In the present application, in the loading sagger, the thickness of the sintered material is h1, the thickness of the mixed material is h2, and h1 and h2 satisfy the following relationship: 5≤h2 / h1≤18. The sintered material laid in the sagger can be used as an isolation layer between the mixed material and the sagger. The mixed material, as the main raw material for preparing sodium positive electrode materials, can provide excellent electrical properties for the positive electrode materials. By controlling the ratio of h2 / h1 within the above range, on the one hand, it can avoid the poor crystallinity and serious capacity loss of the positive electrode material caused by excessive use of sintered material, and on the other hand, it can avoid shortening the life of the sagger due to excessive use of mixed material. As some examples, the ratio of h2 / h1 can be 5.5, 6.0, 6.5, 6.8, 7, 7.1, 7.2, 7.5, 7.7, 7.9, 8, 8.2, 8.5, 8.9, 9, 9.2, 9.5, 10, 11, 12, 13, 14, 16, etc.

[0060] In some embodiments, a=0.45-0.7, b=0.95-1.05, 6<h2 / h1≤16.

[0061] The present application does not particularly limit the shape of the sagger used, for example, it can be a square sagger, a cylindrical sagger, or an elliptical sagger. In addition, the material of the sagger can include high temperature resistant ceramics, for example, a ceramic sagger including at least two of cordierite, mullite, and spinel.

[0062] In some embodiments, the sagger is a ceramic sagger. This type of sagger is low in cost, and the charging method of the present application is simple and easy, which can effectively extend the service life of this type of sagger and inhibit the contamination of the sagger to the positive electrode material, thereby realizing the mass production of sodium positive electrode materials. Generally, in the chemical composition of the ceramic sagger, the aluminum oxide content is above 25wt%.

[0063] In some embodiments, Figure 1 As shown, the sagger is a square open sagger, and the specifications of the sagger are a×b×h t , a is 300~350mm, b is 300~350mm, h t The thickness of the sintered material is h1, which is 5 to 15 mm, the thickness of the mixed material is h2, and the total thickness of the charge is h, which is the value of the sagger h. t The difference between the opening height.

[0064] In the present application, the laying thickness of the sintering material can be selected according to the specifications of the sagger. According to some embodiments, in the charging sagger, the thickness of the sintering material is h1, which is 5 to 15 mm, such as 5 mm, 7 mm, 7.5 mm, 8 mm, 8.5 mm, 9 mm, 10 mm, 12 mm, 13 mm, 15 mm, etc.; the total charging thickness h (h = h1 + h2) is 70 to 100 mm, such as 70 mm, 75 mm, 80 mm, 85 mm, 88 mm, 90 mm, 92 mm, 95 mm, 98 mm, 100 mm, etc. In addition, the total charging thickness h can be less than the height of the sagger, or it can be equal to the height of the sagger (that is, the sagger is filled with materials).

[0065] According to some specific implementations, in step (2), the method of loading the sagger includes the following process:

[0066] The powder of the sintering material is loaded into the sagger, so that the powder is spread evenly and covers the bottom of the sagger, and after compaction, an isolation layer with a thickness of h1 is formed; then the powder of the mixed material is filled into the sagger, so that the powder is spread evenly and covers the isolation layer, and after compaction, a raw material layer with a thickness of h2 is formed to obtain a loaded sagger. The powder can be spread evenly by means of scraping, shaking, vibrating, etc.

[0067] According to the present application, in step (3), the sintering of the charging sagger can be carried out in an oxygen-containing atmosphere. According to some embodiments, the sintering temperature is 900-1000°C, such as 900°C, 910°C, 950°C, 960°C, 970°C, 985°C, 1000°C, etc.; the sintering time is 15-30h, such as 15h, 16h, 17h, 18h, 19h, 20h, 22h, 23h, 24h, 25h, 27h, 30h, etc.

[0068] In the present application, the sintering can be performed in various sintering furnaces, such as a box furnace or a roller furnace. The sintering furnace can also be used to sinter a plurality of charging saggers at the same time to improve production efficiency.

[0069] In some embodiments, the sintering furnace is a high-temperature roller furnace, which can be used to sinter multiple charging saggers at the same time. The high-temperature roller furnace includes a sintering zone, and the temperature of the sintering zone is 900-1000°C.

[0070] In the present application, during the sintering process, the sodium source and metal precursor in the mixture mainly react to form the positive electrode material, and a small amount of sodium ions diffuse into the sintered material at the bottom and are received by the sodium-deficient phase, which can also increase the sodium content of the material in this area, so that the prepared sodium positive electrode material has a higher capacity.

[0071] In some embodiments, the method further comprises: crushing and pulverizing the sintered product to obtain a median particle size Dv 50 It is a sodium battery positive electrode material with a particle size of 5 to 8 μm.

[0072] In some embodiments, the sodium-based positive electrode material is an O3-type sodium-based layered oxide.

[0073] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application.

[0074] In the following examples and comparative examples,

[0075] 1. Nickel-iron-manganese precursor (Ni 0.34 Fe 0.33 Mn 0.33 (OH)2) was synthesized according to the following method:

[0076] A nickel sulfate solution, a ferrous sulfate solution and a manganese sulfate solution are prepared into a nickel-iron-manganese metal salt solution with a concentration of 2 mol / L according to a Ni / Fe / Mn molar ratio of 0.34:0.33:0.33; in addition, a 2 mol / L ammonia complexing agent solution and a 2 mol / L sodium hydroxide solution are prepared;

[0077] The nickel-iron-manganese metal salt solution, ammonia complexing agent solution and sodium hydroxide solution were added to the reactor at a uniform rate of 40 L / h, 4 L / h and 10 L / h respectively, and reacted at 50 ° C under stirring until particles with a particle size of Dv were formed. 50 The precipitate product is 5 μm, which is washed and dried to obtain Ni 0.34 Fe 0.33 Mn 0.33 (OH)2.

[0078] 2. Nickel-cobalt-manganese precursor (Ni 0.34 Co 0.33 Mn 0.33 (OH)2) was synthesized according to the following method:

[0079] A nickel sulfate solution, a cobalt sulfate solution and a manganese sulfate solution are prepared into a nickel-cobalt-manganese metal salt solution with a concentration of 2 mol / L according to a Ni / Co / Mn molar ratio of 0.34:0.33:0.33; a 2.3 mol / L sodium hydroxide solution is used as a precipitant, and a 0.1 mol / L diammonium phosphate solution is used as a complexing agent;

[0080] The nickel-cobalt-manganese metal salt solution, precipitant and complexing agent were added into the reactor at a uniform rate of 40 L / h, 4 L / h and 10 L / h respectively, and reacted at 60 °C under stirring until particles with a particle size of Dv 50 The precipitate product is 5 μm, and after washing and drying, Ni 0.34 Co 0.33 Mn 0.34 (OH)2.

[0081] In the synthesis of the above two precursors, the solutions used are all water-based as solvent.

[0082] 3. Sagger: Cordierite-mullite ceramic sagger; Specifications: length 30mm × width 330mm × height 100mm, opening 15mm.

[0083] 4. Performance test of sodium battery positive electrode materials

[0084] (1) Preparation of sodium button cells

[0085] The sodium positive electrode material, the conductive agent acetylene black, the binder polytetrafluoroethylene (PVDF) are mixed with an appropriate amount of NMP in a mass ratio of 7:2:1 and ground into a uniform slurry. The positive electrode slurry is evenly coated on the surface of an aluminum foil (thickness of 15 μm), and then dried and punched to obtain a positive electrode sheet with a positive electrode film layer thickness of 120 μm.

[0086] Negative electrode sheet: sodium sheet (thickness 600μm);

[0087] Diaphragm: glass fiber membrane (thickness 40 μm);

[0088] Electrolyte: NaClO4 electrolyte with a concentration of 1 mol / L, the solvent is composed of propylene carbonate (PC) and fluoroethylene carbonate (FEC) in a mass ratio of 19:1.

[0089] The positive electrode sheet, separator and negative electrode sheet are cut and assembled in a glove box, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. The separator is soaked with electrolyte and compacted to obtain a button-type sodium battery.

[0090] (2) Capacity test

[0091] The sodium battery was charged to 4.05V at a constant current of 1C at 25°C, then charged at a constant voltage of 4.0V until the current dropped to 0.05C, and then discharged to 1.5V at a constant current of 1C to obtain the first cycle discharge capacity; this charging and discharging was repeated until the 50th cycle, and the discharge capacity of the sodium battery after 50 cycles was obtained.

[0092] Preparation Example 1

[0093] This preparation example is used to illustrate the preparation method of sintering materials and mixed materials.

[0094] Preparation of sintering materials: Na2CO3 and Ni were respectively prepared according to the Na / Me molar ratio a of 0.45, 0.65 and 0.85. 0.34 Fe 0.33 Mn 0.33 The (OH)2 was prepared and mixed evenly, and loaded into different saggers respectively, and then vibrated and cut into blocks. The three saggers were sent together to a roller kiln for sintering. The kiln was an oxygen atmosphere, and the temperature of the sintering zone was controlled to be 950°C. The kiln was sintered at 950°C for 20 hours. The obtained sintered material blocks were crushed and powdered to obtain low sodium ratio positive electrode materials, which were respectively recorded as material A, material B and material C.

[0095] Preparation of mixed material: Na2CO3 and Ni 0.34 Fe 0.33 Mn 0.33 (OH)2 is mixed evenly on a high-speed mixer to obtain a mixture, which is respectively recorded as material D and material E.

[0096] Examples 1-2, Comparative Examples 1-2

[0097] Prepare 4 new saggers to be loaded, marked as No. 1, No. 2, No. 3, and No. 4 respectively.

[0098] S1: Load the four saggers separately. The loading conditions are as follows:

[0099] No. 1 sagger: filled with mixed material D (material layer thickness 85 mm);

[0100] No. 2 sagger: Spread 10mm of material A on the bottom, scrape and compact it, and then fill it with mixed material D;

[0101] No. 3 sagger: spread 10mm of material B on the bottom, scrape and compact it, and then fill it with mixed material D;

[0102] No. 4 sagger: Spread 10mm of material C on the bottom, scrape and compact it, and then fill it with mixed material D.

[0103] S2: Sintering to prepare sodium cathode materials

[0104] The sagger loaded in the above manner is vibrated and cut into pieces, and then simultaneously placed in a roller kiln for sintering, the temperature of the sintering zone is controlled to be 950°C, and sintered at 950°C for 20 hours, and the kiln is an oxygen atmosphere;

[0105] The sagger is turned over to separate the sintered material blocks, and the obtained sintered material blocks are roughly crushed by rollers and air flow crushing to obtain Dv 50 It is a sodium battery positive electrode material with a thickness of 5.5μm.

[0106] S3: Repeat steps S1 to S2

[0107] In the process of S2, the bottom and four sides of the sagger are observed and analyzed for cracking. If any of the four saggers show obvious cracking (crack length > 10 mm, the same below), the verification is stopped; if no cracking occurs, steps S1 to S2 are repeated to cycle into the furnace for verification, and each time entering the furnace is counted as one time and accumulated in sequence.

[0108] The service life of the sagger is the number of times it is reused until it cracks minus 1.

[0109] The charging conditions, service life and electrical properties of the sodium cathode materials prepared in the first furnace of the four saggers are shown in Table 1.

[0110] Table 1

[0111]

[0112] Combined with Table 1, it can be seen that the No. 1 sagger (Comparative Example 1) without sintering material at the bottom cracked after being used once, indicating that the direct use of a high sodium ratio mixture to prepare the sodium positive electrode material makes it easy for sodium ions to penetrate into the pores of the sagger and react with the sagger to cause the sagger to crack; and the No. 4 sagger (Comparative Example 2) with a higher sodium ratio material laid on the bottom also cracked after being used twice. The reason is that the sodium ratio of the bottom material is relatively high, lacks sodium vacancies, and cannot absorb free sodium diffused from the mixture, causing sodium ions to eventually penetrate into the No. 4 sagger to participate in the reaction and cause the sagger to crack; the number of uses of No. 2 and No. 3 saggers increased significantly, and the capacity performance was good, and was equivalent to the capacity of the sodium positive electrode material prepared in Comparative Example 1, indicating that laying a certain thickness of low sodium ratio sintering material at the bottom can effectively improve the corrosion and cracking problem of the sagger without affecting the capacity.

[0113] Example 3 and Comparative Example 3

[0114] Prepare two new saggers for loading, marked as No. 5 and No. 6 respectively.

[0115] S1: Load the two saggers separately. The loading conditions are as follows:

[0116] No. 5 sagger: Spread 30mm of material B on the bottom, scrape and compact it, and then fill it with mixed material D;

[0117] No. 6 sagger: Spread 8mm material A on the bottom, scrape and compact it, and then fill it with mixed material D;

[0118] S2: Sintering to prepare sodium cathode materials

[0119] The sagger loaded in the above manner is vibrated and cut into pieces, and then simultaneously placed in a roller kiln for sintering, the temperature of the sintering zone is controlled to be 950°C, and sintered at 950°C for 20 hours, and the kiln is an oxygen atmosphere;

[0120] The sagger is turned over to separate the sintered material blocks, and the obtained sintered material blocks are roughly crushed by rollers and air flow crushing to obtain Dv 50 It is a sodium battery positive electrode material with a thickness of 5.5μm.

[0121] S3: Repeat steps S1 to S2

[0122] In the process of S2, the bottom and four sides of the sagger are observed and analyzed for cracking. If any of the two saggers show obvious cracking, the verification is stopped; if no cracking occurs, steps S1 to S2 are repeated to cycle into the furnace for verification, and each time entering the furnace is counted as one time and accumulated in sequence.

[0123] The service life of the sagger is the number of times it is reused until it cracks minus 1.

[0124] The charging conditions, service life and electrical properties of the sodium cathode materials prepared in the first furnace of the two saggers are shown in Table 2.

[0125] Table 2

[0126]

[0127] For the sake of comparison, Table 2 also lists the effects of Comparative Example 1 and Example 2. It can be seen from Table 2 that the No. 1 sagger without sintering material at the bottom cracked after being used once, and the number of uses of No. 3 and No. 6 saggers (Example 3) increased. In addition, by comparing No. 3 and No. 5 saggers (Comparative Example 3), it can be seen that under the condition of using the same sintering material (the same value of a), as the laying thickness of the sintering material increases, the service life of the sagger will increase, but it can be seen from Comparative Example 3 that when the laying thickness of the sintering material is too high, the capacity of the prepared sodium positive electrode material is significantly reduced. This is because the laying thickness of the sintering material in the No. 5 sagger is too high, resulting in the sodium ions diffused from the upper mixed material being unable to completely supplement the sodium vacancies, affecting the performance of the sodium positive electrode material.

[0128] Figure 2The XRD spectra of the sodium positive electrode materials prepared in Comparative Example 1, Example 2 and Comparative Example 3 show that there is a characteristic peak of 003 of the O3 phase at 16.8° and a characteristic peak of 104 of the O3 phase near 42°, indicating that O3 phase layered oxygen compounds have been synthesized. However, the 003 / 104 peak intensity ratio of the 30mm sintered material (Comparative Example 3) at the bottom is weaker than that of the other two groups, and the crystallinity is poor. It can be seen that the sintered material of Comparative Example 3 did not fully react in the No. 5 sagger, resulting in serious capacity loss.

[0129] Examples 4 to 6 and Comparative Example 4

[0130] Prepare 4 new saggers to be loaded, marked as No. 7, No. 8, No. 9, and No. 10 respectively.

[0131] S1: Load the four saggers separately. The loading conditions are as follows:

[0132] No. 7 sagger: directly filled with mixed material E;

[0133] No. 8 sagger: Spread 5mm material A on the bottom, scrape and compact it, and then fill it with mixed material E;

[0134] No. 9 sagger: Spread 10mm of material B on the bottom, scrape and compact it, and then fill it with mixed material E;

[0135] No. 10 sagger: Spread 8mm material B on the bottom, scrape and compact it, and then fill it with mixed material E.

[0136] S2: Sintering to prepare sodium cathode materials

[0137] The sagger loaded in the above manner is vibrated and cut into pieces, and then simultaneously placed in a roller kiln for sintering, the temperature of the sintering zone is controlled to be 950°C, and sintered at 950°C for 20 hours, and the kiln is an oxygen atmosphere;

[0138] The sagger is turned over to separate the sintered material blocks, and the obtained sintered material blocks are roughly crushed by rollers and air flow crushing to obtain Dv 50 It is a 6μm sodium battery positive electrode material.

[0139] S3: Repeat steps S1 to S2

[0140] In the process of S2, the bottom and four sides of the sagger are observed and analyzed for cracking. If any of the four saggers show obvious cracking, the verification is stopped; if no cracking occurs, steps S1 to S2 are repeated to cycle into the furnace for verification, and each time entering the furnace is counted as one time and accumulated in sequence.

[0141] The service life of the sagger is the number of times it is reused until it cracks minus 1.

[0142] The loading conditions, service life and electrical properties of the sodium cathode materials prepared in the first furnace of the four saggers are shown in Table 3.

[0143] Table 3

[0144]

[0145] It can be seen from Table 3 that in order to prepare sodium cathode materials with the same target sodium ratio, after laying a sintering material of appropriate thickness on the bottom of the sagger, the service life of the sagger can be significantly improved while maintaining the electrical properties of the sodium cathode materials.

[0146] Preparation Example 2

[0147] This preparation example is used to illustrate the preparation method of sintering materials and mixed materials.

[0148] Preparation of sintering material: Na2CO3 and Ni 0.34 Co 0.33 Mn 0.33 The (OH)2 are mixed and loaded into different saggers respectively, then vibrated and cut, and the two saggers are sent to a roller kiln for sintering. The kiln is an oxygen atmosphere, and the temperature of the sintering zone is controlled to 980℃, and sintered at 980℃ for 25h. The obtained sintered material blocks are crushed and powdered to obtain low sodium ratio positive electrode materials, which are respectively recorded as material F and material G.

[0149] Preparation of the mixture: Na2CO3 and Ni 0.34 Co 0.33 Mn 0.33 The (OH)2 ingredients are mixed evenly on a high-speed mixer to obtain a mixture, which is recorded as material H.

[0150] Example 7 to Example 8 and Comparative Example 5

[0151] Prepare three new saggers for loading, marked as No. 11, No. 12, and No. 13 respectively.

[0152] S1: Load the three saggers separately. The loading conditions are as follows:

[0153] No. 11 sagger: directly filled with mixed material H;

[0154] No. 12 sagger: Spread 6mm material F on the bottom, scrape and compact it, and then fill it with mixed material H;

[0155] No. 13 sagger: Spread 12mm material G on the bottom, scrape and compact it, and then fill it with mixture H.

[0156] S2: Sintering to prepare sodium cathode materials

[0157] The sagger loaded in the above manner is vibrated and cut into pieces, and simultaneously placed in a roller kiln for sintering, the temperature of the sintering zone is controlled to be 950°C, and sintered at 950°C for 24 hours, and the kiln is an oxygen atmosphere;

[0158] The sagger is turned over to separate the sintered material blocks, and the obtained sintered material blocks are roughly crushed by rollers and air flow crushing to obtain Dv 50 It is a sodium battery positive electrode material with a thickness of 5.5μm.

[0159] S3: Repeat steps S1 to S2

[0160] In the process of S2, the bottom and four sides of the sagger are observed and analyzed for cracking. If any of the three saggers show obvious cracking, the verification is stopped; if no cracking occurs, steps S1 to S2 are repeated to cycle into the furnace for verification, and each time entering the furnace is counted as one time and accumulated in sequence.

[0161] The service life of the sagger is the number of times it is reused until it cracks minus 1.

[0162] The loading conditions, service life and electrical properties of the sodium cathode materials prepared in the first furnace of the three saggers are shown in Table 4.

[0163] Table 4

[0164]

[0165] It can be seen from Table 4 that for sodium-based cathode materials with the same target sodium ratio, after laying appropriate thicknesses of sintered materials with different low sodium ratios on the bottom, the service life of the sagger can be significantly improved while maintaining the electrical properties of the sodium-based cathode materials.

[0166] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A method for preparing a sodium positive electrode material, characterized in that: include: (1) Provide sintering materials and mixed materials The sintering material is a sintering product of a sodium source and a metal precursor, and the molar ratio of the sodium source to the metal precursor is Na / Me, which is a; The mixed material is a mixture of a sodium source and a metal precursor, and the molar ratio of the sodium source to the metal precursor is calculated as b with Na / Me; a=0.4~0.7,b=0.9~1.1,Me represents the metal element in the metal precursor; (2) Sagger loading A layer of sintering material is laid on the bottom of the sagger, and then the mixed material is loaded on the sintering material, and the mixed material is cut into pieces to obtain a loading sagger; In the charging sagger, the thickness of the sintering material is h1, the thickness of the mixed material is h2, and h1 and h2 satisfy the following relationship: 5≤h2 / h1≤18; (3) sending the loading sagger to a sintering furnace for sintering to form a sodium positive electrode material.

2. The preparation method according to claim 1, characterized in that: In the charging sagger, the thickness of the sintering material h1 is 5-15 mm, the total charging thickness h=h1+h2, and h is 70-100 mm.

3. The preparation method according to claim 1 or 2, characterized in that: The metal element Me in the metal precursor is selected from one or more of Ni, Fe, Mn, Co, Al, Ti, Mg, Ca, Zn, Cu, W and La.

4. The preparation method according to any one of claims 1 to 3, characterized in that The metal precursor is a nickel-containing ternary precursor; Preferably, the chemical formula of the nickel-containing ternary precursor is Ni x M y A 1-x-y (OH)2, wherein M is Fe or Co, A is Mn or Ti, 0.2≤x≤0.6, 0.1<y<0.

4.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The sodium source is sodium carbonate and / or sodium hydroxide.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The sintering material is prepared by a method comprising the following steps: In the presence of an oxygen-containing atmosphere, the sodium source and the metal precursor are subjected to high-temperature calcination and crushing to powder; wherein the high-temperature calcination temperature is 800-900° C. and the time is 15-30 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The sintering is carried out in an oxygen-containing atmosphere, the sintering temperature is 900-1000° C., and the sintering time is 15-30 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The sintering furnace is a high-temperature roller furnace, which includes a sintering zone, and the temperature of the sintering zone is 900-1000°C.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The sagger is a ceramic sagger; Preferably, the material of the ceramic sagger includes at least two of cordierite, mullite and spinel.

10. The preparation method according to any one of claims 1 to 9, characterized in that: a=0.45~0.7, b=0.95~1.05, 6<h2 / h1≤16.

Citation Information

Patent Citations

  • Preparation method of lithium cobaltate cathode material, and sagger

    CN108423715A

  • Preparation method of lithium nickel cobalt manganate positive electrode material and saggar

    CN108649216A

  • Preparation method of sagger for sintering sodium-ion battery positive electrode material

    CN117164368A

  • Positive electrode active material, electrochemical apparatus, and electronic device

    US20230299275A1